IMPROVING THE EFFICIENCY OF THE CLASSIFIED OBJECT PROTECTION SYSTEM (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article contains the categorized objects in the curfew system proposals and methods for improving engineering and technical means of protection lit.